Impact of Match Type and Match Halves on Referees’ Physical Performance and Decision-Making Distance in Chinese Football Super League - Jiang, Jinying; Ge, Huanmin; Du, Lida; Gomez, Miguel-Angel; Gong, Bingnan; Cui, Yixiong (Frontiers in Psychology, 2022)
The purpose of this study was to explore how Chinese Football Super League (CSL) referees’ physical performance and decision-making distance varied according to match type and match halves. Data from 108 matches played by top-4 ranked and bottom-4 ranked teams during 2018 to 2019 CSL seasons were collected. Level of matches were classified into three groups: a. upper-ranked (top-4) teams against top-4 teams, b. top-4 teams against lower-ranked teams (bottom-4), and c. bottom-4 teams against bottom-4 teams. Two-way ANOVA and Scheirer-Ray-Hare test (p<0.05) were used to examine the statistical differences of referees’ physical and spatial related distance variables among different match levels and halves. The Euclidean distance to the ball at the following three events were statistically different among three match types: clearance (p=0.03, E_R^2=0.03), running with ball (p=0.01, E_R^2=0.04) and shot off target (p=0.04, E_R^2=0.03). Additionally, referees’ distance to the ball at three events were statistically different between both match halves: pass (p<0.001, r=0.69), reception (p<0.001, r=0.76) and running with ball (p<0.001, r=0.77). Total running distance was statistically different between both match halves (p=0.001, d=0.05). The findings indicated that although CSL referees showed little difference in physical performance when officiating matches of three competitive levels and two halves, distinct rhythms of competitions determined that they needed to adjust running strategies so as to maintain proper distance to the ball. The current study implied that the CSL referees’ match performance was affected by teams’ style of play and match status.